2008
DOI: 10.1042/bj20071646
|View full text |Cite
|
Sign up to set email alerts
|

A cyclic peptidylic inhibitor of murine urokinase-type plasminogen activator: changing species specificity by substitution of a single residue

Abstract: uPA (urokinase-type plasminogen activator) is a potential therapeutic target in a variety of pathological conditions, including cancer. In order to find new principles for inhibiting uPA in murine cancer models, we screened a phage-displayed peptide library with murine uPA as bait. We thereby isolated several murine uPA-binding peptide sequences, the predominant of which was the disulfide-bridged constrained sequence CPAYSRYLDC, which we will refer to as mupain-1. A chemically synthesized peptide corresponding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 29 publications
2
42
0
Order By: Relevance
“…Thus, upain-1 binds approximately 500-fold better to human uPA than to murine uPA, whereas mupain-1 binds more than 2000-fold better to murine uPA than to human uPA. Both bind very selectively to uPA compared with other serine proteases from the same species (Hansen et al, 2005;Andersen et al, 2008). Analysis of the inhibitory mechanism showed that both upain-1 and mupain-1 are competitive inhibitors of their target enzymes (Hansen et al, 2005;Andersen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, upain-1 binds approximately 500-fold better to human uPA than to murine uPA, whereas mupain-1 binds more than 2000-fold better to murine uPA than to human uPA. Both bind very selectively to uPA compared with other serine proteases from the same species (Hansen et al, 2005;Andersen et al, 2008). Analysis of the inhibitory mechanism showed that both upain-1 and mupain-1 are competitive inhibitors of their target enzymes (Hansen et al, 2005;Andersen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Two-chain murine uPA was purchased from Molecular Innovations (Novi, MI). Wild-type and mutant recombinant human and murine uPA were expressed in and in some cases purified from human embryonic kidney 293T cells transfected with the corresponding cDNAs in pcDNA3.1 (Petersen et al, 2001;Andersen et al, 2008).…”
Section: Exosite Interactions Of Peptidylic Serine Protease Inhibitormentioning
confidence: 99%
See 3 more Smart Citations